DRIS I: development of DRIS indices in oil palm cultivation (2023)
Nutritional diagnosis based on foliar tissue analysis is an efficient tool for detecting nutritional imbalances and aiding in the fertilizer recommendation process. Therefore, the objective of this study was to use this information to implement the Diagnosis and Recommendation Integrated System (DRIS), a method that uses the relationships between nutrients and their respective coefficients of variation in a high-productivity population, establishing the norms. In this study, DRIS norms and indices were developed for the oil palm crop, specifically the IRHO hybrid, in the central palm region of Colombia. A total of 113 samples were taken, of which 28 were considered representative of the population with high yields in fresh palm fruit production, exceeding 32.9 tons per hectare. The selection of DRIS norms was based on the criteria of the highest variance ratio and the "R" value criterion. The decreasing order of deficiency constraints for foliar tissue concentrations is Fe>Zn>S>P>Cl>Mg>B>Na>K>Ca>Cu=Mn>N, with Iron and Zinc being the limiting elements due to deficiency, and Nitrogen due to excess. Small changes in sulfur concentrations have a significant impact on yield.